Heavy metal accumulation in Halimione portulacoides: Intra- and extra-cellular metal binding sites - Sousa, Ana I. (2008)
Salt marsh plants can sequestrate and inherently tolerate high metal concentrations found in salt marsh sediments. This work intended to understand the Halimione portulacoides (L.) Aellen strategies to prevent metal toxicity, by investigating the metal location in different plant organs and in the cell. A sequential extraction was performed on leaves, stems and roots of H. portulacoides in order to determine and compare the metal (Zn, Pb, Co, Cd, Ni and Cu) concentration in several fractions of the plant material (ethanolic, aqueous, proteic, pectic, polissacaridic, lenhinic and cellulosic). This study shows that all plant organs of H. portulacoides mostly retain metals in the cell wall (65% is the average for all studied metals stored in the root cell wall, 55% in the stems and 53% in the leaves), and the metal content in the intracellular compartment is much lower (21% in roots, 25% in stems and 32% in leaves). High levels of heavy metal in the sedimentary environment do not cause toxicity to H. portulacoides, because H. portulacoides immobilizes them in different cell compartments (cell wall + proteic fraction + intracellular) outside key metabolic sites.